Escherichia coli from Crohn’s disease patient displays virulence features of enteroinvasive (EIEC), enterohemorragic (EHEC), and enteroaggregative (EAEC) pathotypes - Silva Santos, Ana Carolina da [UNESP]; Romeiro, Fernando Gomes [UNESP]; Sassaki, Ligia Yukie [UNESP]; Rodrigues, Josias [UNESP] (Biomed Central Ltd, 2015)
Background: Escherichia coli is a normal inhabitant of the gut which upon acquiring virulence factors becomes potentially able to cause diseases. Although Eschericia coli population augments in Crohn's disease (CD), the reason of this proliferation is not yet clear. CD associated Escherichia coli shows features of extraintestinal pathogenic categories (ExPEC), and eventually the ability to invade cultured epithelial cells, a property observed among diarrheagenic Escherichia coli (DEC). In this work, data on the characterization of an Escherichia coli isolate from a CD patient reveal that, besides invasiveness, CD associated Escherichia coli may harbor other typical DEC markers, namely those defining enterohemorragic (EHEC) and enteroaggregative (EAEC) pathotypes.Results: The studied strain, detected both in an ileum biopsy and stools, belonged to the B2 Escherichia coli reference collection (EcoR) phylogroup and harbored the intimin, Shiga cytotoxin 1, and AggR transcriptional activator encoding genes (eae, stx1, aggR, respectively); displayed aggregative adherence to Hep-2 cells and an ability to enter Caco-2 cells four times as high as that of EIEC reference strain and half of invasiveness of AIEC LF82. It was able to enter and replicate in J774 macrophages with invasiveness 85 times as high as that of LF82, but with only one sixth of the intracellular proliferation ability of the later. Extracellular products with cytotoxic activity on Vero cells were detected in strain's cultures. Preliminary analysis indicated similarity of this strain's genome with that of O104:H4/2011C-3493.Methods: Following its isolation from a resected CD patient, the strain was characterized by in vitro adhesion and invasion assays to Hep-2, invasion to Caco-2 cells and to J774 macrophages and tested for the ability to form biofilm and to produce Shiga cytotoxins. PCRs were carried out to identify virulence genetic markers and for EcoR phylogrouping. The strain's genome was sequenced by means of Ion torrent PGM platform.Conclusion: The detection, in a CD patient, of an Escherichia coli combining virulence features of multiple DEC pathotypes seems not only to stress the relevance of Escherichia coli to CD etiopathogenesis but also to indicate the existence of new and potentially more virulent strains putatively associated with this disease.
Keywords: Escherichia coli; Crohn's disease; Invasive; MLST; Serotype; Adherence; Virulence